Prevention & Control of Neglected Tropical Diseases : Our Dreams & Achievements - Khandaker, Md Abul Kashem (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3329/jom.v9i2.1431Â  J MEDICINE 2008; 9 : 64-65